Effect of Management in controlling necrotic enteritis in poultry - Waseem Akram; Muhammad Zain Kaleem; Muhammad Hamza; Samad, Abdul; Mishal Fatima (Information Technology and Science (ITScience), 2023)
The prohibition of antibiotic growth promoters has an unavoidable impact on the intestinal environment of chickens. The biggest challenge to the chicken business has been the resurgence of necrotic enteritis, which inhibits growth and feed conversions in preclinical forms and produces high mortality in its clinical form. In terms of performance, welfare, and mortality, it has been one of the most prevalent and economically damaging bacteria infections in contemporary broiler flocks. A multi-factorial disease process known as necrotizing enteritis occurs when many co-factors are often needed to start a disease outbreak. Clostridium perfringens is now identified as the disease's etiological agent, it is unclear whether predisposing conditions cause excessive C. perfringens growth and subsequent development of the disease. Any condition that stresses broiler chicks could impair the intestinal ecosystem's balance and weaken the immune system, increasing the chance of an epidemic of NE. The management of poultry may have a significant impact on NE pathogenesis. For instance, feed limitation and vaccination against coccidiosis can guard against NE, but high stocking densities, excessive house temperatures, and feed mycotoxins can predispose to NE. Understanding the disease's pathophysiology and the linkages between dietary, nutritional, and viral factors and the emergence of necrotic enteritis become extremely crucial. In order to imply managerial methods at the farm level to minimize the occurrence and the severity of the disease in the post-antibiotic era, this is essential and crucial.